2013
DOI: 10.1103/physrevb.88.054506
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic x-ray study of phonon broadening and charge-density wave formation in ortho-II-ordered YBa2Cu3O6.54

Abstract: Inelastic x-ray scattering is used to investigate charge-density wave (CDW) formation and the low-energy lattice dynamics of the underdoped high-temperature superconductor ortho-II YBa 2 Cu 3 O 6.54 . We find that, for a temperature ∼1/3 of the CDW onset temperature (≈155 K), the CDW order is static within the resolution of the experiment, that is the inverse lifetime is less than 0.3 meV. In the same temperature region, low-energy phonons near the ordering wave vector of the CDW show large increases in their … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 46 publications
(143 reference statements)
3
61
0
Order By: Relevance
“…Thus it appears that the wavevectors of the phonon anomalies and the charge ordering peaks observed here have a common origin. We would also ex- pect further temperature-dependent anomalies in the acoustic phonons as recently observed 8,9 in YBCO. It is widely believed that the spin and charge correlations in cuprates are closely related.…”
Section: B Incommensurability Correlation Lengths and Temperature Dmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus it appears that the wavevectors of the phonon anomalies and the charge ordering peaks observed here have a common origin. We would also ex- pect further temperature-dependent anomalies in the acoustic phonons as recently observed 8,9 in YBCO. It is widely believed that the spin and charge correlations in cuprates are closely related.…”
Section: B Incommensurability Correlation Lengths and Temperature Dmentioning
confidence: 55%
“…For example, in YBa 2 Cu 3 O 6+x , charge order has been detected in magnetic fields 15 T by NMR 5,6 and ultrasound 7 indicating that it is essentially static. X-ray experiments 1,2 observe incommensurate charge density wave order in zero field which may only fluctuate on frequency scales less than ∼1 meV 8,9 . Taken together, these experiments suggest that incommensurate charge correlations appear below the pseudogap temperature, compete with the superconductivity and become static in magnetic fields 15 T.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative low energy collective charge modes may also be possible. Recent resonant Xray scattering studies on YBCO also found low energy charge fluctuations interpreted as CDW fluctuations 40,41 close to the wave vector of the giant phonon anomaly. Results presented here demonstrate that these collective charge excitations may underlie the superconductivity mechanism, because their signature in the phonon spectra scales with T c .…”
mentioning
confidence: 91%
“…It is notable that we do not see any significant interaction between the stripe fluctuations and the acoustic mode. In contrast to the soft-mode behavior detected in association with the charge-densitywave order in underdoped YBa 2 Cu 3 O 6+x [46,47], we appear to have overlapping dispersions. The slowest dispersion is in the direction perpendicular to the stripes, where the effective velocity is comparable to that of transverse acoustic modes shown in Fig.…”
mentioning
confidence: 51%